2020
DOI: 10.1016/j.heliyon.2020.e03666
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional extraction technique with ultrasound assisted extraction on recovery of phenolic compounds from lemon scented tea tree (Leptospermum petersonii) leaves

Abstract: Leptospermum petersonii is a native Australian medicinal and aromatic plant. This study was designed to evaluate the influence of solvents and ultrasound-assisted extraction (UAE) parameters including time, temperature, and sonication power on the yield of phenolic compounds and antioxidant capacity from lemon scented tea tree leaves. Extraction efficiency of the optimal UAE conditions were compared with that of shaking water bath technique. The results show that extraction solvents significantly affect extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…UG had an obviously higher antioxidant capacity than UW, WG, and WW through DPPH, ABTS, and RA assays, which was due to the cavitation effects’ promoting the mass transfer of TPC to glycerol solutions. Meanwhile, previous studies revealed that the phenolic compounds and the sub-groups of phenolic compounds, such as TFC, TCTC, and TTC, could affect the antioxidant capacity [ 40 ]. In the present work, the highest antioxidant capacities through DPPH, ABTS, and RA assays did also coincide with higher TFC, TCTC, and TTC obtained by UG, which could explain the correlation between the antioxidant activities with polyphenol classes.…”
Section: Resultsmentioning
confidence: 99%
“…UG had an obviously higher antioxidant capacity than UW, WG, and WW through DPPH, ABTS, and RA assays, which was due to the cavitation effects’ promoting the mass transfer of TPC to glycerol solutions. Meanwhile, previous studies revealed that the phenolic compounds and the sub-groups of phenolic compounds, such as TFC, TCTC, and TTC, could affect the antioxidant capacity [ 40 ]. In the present work, the highest antioxidant capacities through DPPH, ABTS, and RA assays did also coincide with higher TFC, TCTC, and TTC obtained by UG, which could explain the correlation between the antioxidant activities with polyphenol classes.…”
Section: Resultsmentioning
confidence: 99%
“…UAE is a green and efficient way to increase mass transfer, requiring reduced quantities of solvent and without specific solvent requirements (Dedousi et al, 2017;Contreras et al, 2020). Additionally, this extraction method is considered a rapid and sustainable alternative to conventional methods and it can be scaled up to industrial scales (Briones-Labarca et al, 2015;Meregalli et al, 2020;Saifullah et al, 2020).…”
Section: Ultrasound-assisted Extractionmentioning
confidence: 99%
“…Ultrasound-assisted extraction (UAE) is an innovative and promising technique used in several fields such as cosmetics, pharmaceutical, chemical, and food industries since the second half of the 20 th century [22]. Recently, several studies indicate that ultrasound produces more abundant extracts in biomolecules and in a shorter extraction time compared to conventional extraction techniques [22,23]. A study realized by Chemat et al [24] showed that the yield of carvone extracted from caraway seeds (Carum carvi L.) is best in ultrasound-assisted extraction as those given by the Soxhlet extract.…”
Section: Introductionmentioning
confidence: 99%